Binuclear Macrocyclic Complexes of Ni(II), Co(II), Fe(II) and Cu(II) with 3,4,7,8,14,15,18,19, Octaphenyl 1,2,5,6,9, 10,12,13,16,17,20,21-dodecaaza-Cyclobicosa-3,4,7,8,14,15,18,19-Octaene - Sahu, K.; Thakur, R.S (Asian Journal of Chemistry, 2010)
A series of binuclear macrocyclic complexes have been synthesised by the action of formaldehyde on tetra chloro, tetra bromo, tetra iodo and tetra thiocyanato bis-(l,2,5,6-tetra phenyl-1,6-dioxo-3,4-diazahexa-2,4-diene, 1,6-dihydrazone) dinickel(II), dicobalt(II), diiron(II) and dicopper(II). Structures of these complexes have been elucidated on the basis of IR and electronic spectra.